Potong Pele Stunting melalui Pelatihan Kader tentang Pemberian Makan Bayi dan Anak (PMBA) Berbasis Pangan Lokal: Potong Pele Stunting through Cadre Training on Local Food-Based Feeding of Infants and Children - Muhamad Asrar; Ety Yuni Ristanti; Michran Marsaoly (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Potong pele stunting is the slogan used by the Maluku government in handling stunting in Maluku. Central Maluku Regency is the district with the highest prevalence of stunting, which was 15,9% in 2020, and has been a locus of stunting since 2019. This community service aims to train posyandu cadres in providing counseling on local food-based infant and young child feeding (IYCF) and monitoring growth. The methods used are training, practice, monitoring, and evaluation. The number of cadres trained was 18 people. The results of the service showed an increase in the knowledge of cadres as indicated by the level of knowledge of the majority of participants before being given training in the less category as much as 70%. After being given training, most of them had sufficient (55%) and good (40%) levels of knowledge. Cadres are skilled in counseling mothers of toddlers about local food-based feeding infants and young children and monitoring growth.